2023
DOI: 10.1039/d3cc00708a
|View full text |Cite
|
Sign up to set email alerts
|

Diastereo- and enantioselective synthesis of biaryl aldehydes bearing both axial and central chirality

Abstract: We describe herein an intriguing method for the synthesis of biaryl aldehydes bearing both axial and central chirality through a desymmetric [3+2] cycloaddition reaction of activated isocyanides with prochiral biaryl...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In the proposed mechanism (Scheme 27b), the reductive quenching process of the photoexcited 4CzIPN* by Hantzsch ester (HE) led to 4CzIPN *À , which produced Co Nearly at the same time, Qian, Liao, and co-workers developed an Ag/L-catalyzed desymmetric (3 + 2) cycloaddition of prochiral biaryl dialdehydes 1 with activated isocyanides 2 to access a series of biaryl aldehydes 3 bearing a stereogenic CÀ C axis and two adjacent stereogenic carbon centers (Scheme 28). [65]…”
Section: Other Biaryl Atropisomers With C-stereogenic Centersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the proposed mechanism (Scheme 27b), the reductive quenching process of the photoexcited 4CzIPN* by Hantzsch ester (HE) led to 4CzIPN *À , which produced Co Nearly at the same time, Qian, Liao, and co-workers developed an Ag/L-catalyzed desymmetric (3 + 2) cycloaddition of prochiral biaryl dialdehydes 1 with activated isocyanides 2 to access a series of biaryl aldehydes 3 bearing a stereogenic CÀ C axis and two adjacent stereogenic carbon centers (Scheme 28). [65]…”
Section: Other Biaryl Atropisomers With C-stereogenic Centersmentioning
confidence: 99%
“…Nearly at the same time, Qian, Liao, and co‐workers developed an Ag/ L ‐catalyzed desymmetric (3+2) cycloaddition of prochiral biaryl dialdehydes 1 with activated isocyanides 2 to access a series of biaryl aldehydes 3 bearing a stereogenic C−C axis and two adjacent stereogenic carbon centers (Scheme 28). [65] …”
Section: Atropisomers With C‐stereogenic Centersmentioning
confidence: 99%
“…Asymmetric catalysis with NHCs as chiral catalysts has been a powerful organocatalytic tool to construct complex molecular architectures containing central chirality . It was not until recently that much more attention was paid to the construction of axial chirality, and a series of elegant works were reported to deliver C–C and C–N axially chiral compounds through NHC-catalysis . For example, Zhang and Zheng reported an atroposelective synthesis of axially chiral aldehydes by NHC-catalyzed oxidative esterification via a sequential desymmetrization/kinetic resolution process (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the desymmetrization of prochiral compounds has emerged as an efficient and straightforward approach. Therefore, many classic transformations have been conducted in a desymmetric manner, such as reductive couplings of biaryl dialdehydes, Minisci reaction using α-amino acid esters and 5-arylpyrimidines as the coupling partner, [3 + 2] cycloaddition reaction of biaryl dialdehydes, hydroarylation of vinyl ethers or bicycloalkenes, and intramolecular dehydrogenative C–H silylation to access silicon-central and axial chiralities (Scheme B). Very recently, Li et al reported a Co-catalyzed photoreductive enantioselective desymmetric functionalization of dialdehyde to deliver axially and centrally chiral diaryl ethers …”
mentioning
confidence: 99%